2009
DOI: 10.1128/jcm.01891-08
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm Formation by Staphylococcus haemolyticus

Abstract: Infections due to coagulase-negative staphylococci (CoNS) most frequently occur after the implantation of medical devices and are attributed to the biofilm-forming potential of CoNS. Staphylococcus haemolyticus is the second most frequently isolated CoNS from patients with hospital-acquired infections. There is only limited knowledge of the nature of S. haemolyticus biofilms. The aim of this study was to characterize S. haemolyticus biofilm formation. We analyzed the biofilm-forming capacities of 72 clinical S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
164
1
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(190 citation statements)
references
References 50 publications
15
164
1
8
Order By: Relevance
“…In relation to MRSHa, 21 (70%) isolates were able to produce biofilm, of which 26.6% of them were classified to be a strong biofilm producer (Table I). Similar to our results, Fredheim et al (2009) found that 74% of the S. haemolyticus analyzed were able to produce biofilms. However, the biofilm formed by S. haemolyticus has not been subject to more detailed studies so far.…”
Section: Biofilm Studysupporting
confidence: 82%
See 1 more Smart Citation
“…In relation to MRSHa, 21 (70%) isolates were able to produce biofilm, of which 26.6% of them were classified to be a strong biofilm producer (Table I). Similar to our results, Fredheim et al (2009) found that 74% of the S. haemolyticus analyzed were able to produce biofilms. However, the biofilm formed by S. haemolyticus has not been subject to more detailed studies so far.…”
Section: Biofilm Studysupporting
confidence: 82%
“…Previous studies have suggested that extracellular proteins seem to be one of the main components of the biofilm matrix formed by S. haemolyticus (Fredheim et al, 2009;Silva et al, 2013). Because of that, we expected papain to disrupt biofilm accumulation produced by MRSHa.…”
Section: Biofilm Studymentioning
confidence: 99%
“…The ability of the S. warneri strains to form biofilm on an abiotic surface was quantified essentially as described elsewhere (Kim et al, 2008;Fredheim et al, 2009). In brief, an overnight culture grown in tryptic soy broth (TSB; Difco, Beckton Dickinson) with 0.25 % glucose at 37 C was diluted 1 : 100 in the medium and 100 µl was transferred into 96-well polystyrene microtiter plates.…”
Section: Methodsmentioning
confidence: 99%
“…Detachment assay was performed as described by Fredheim et al (2009). The major components of S. warneri biofilms were analysed using sodium metaperiodate (NaIO 4 ) to degrade polysaccharide, proteinase K to degrade proteins and DNaseI to degrade DNA.…”
Section: Methodsmentioning
confidence: 99%
“…Most S. haemolyticus strains seem to lack the important virulence attributes. However, some enzymes, cytolysins or surface substances are indicated in the literature as factors contributing to its virulence (Daniel et al, 2014;Flahaut et al, 2008;Simango, 2005), but none of them was identified as a crucial and determinative factor (Fredheim et al, 2009). Despite this, S. haemolyticus is, after S. epidermidis, the second most frequently isolated CNS from clinical cases, particularly from blood infections, including sepsis (Becker et al, 2014;Klingenberg et al, 2007;Liakopoulos et al, 2008;Silva et al, 2013).…”
Section: Introductionmentioning
confidence: 99%